Pengolahan Sampah Plastik Menjadi Bahan Bakar Minyak dengan Menggunakan Proses Pirolisis - Moh. Abiyyu Haidar; Nor Faizeh; Bambang Wahyudi (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
The use of plastic is increasing along with the development of people's economic activities. The problem of plastic waste is still a big scourge in this modern life even though it has been recycled in such a way. Therefore, it is necessary to have a further processing process. One of them is by going through the pyrolysis process. Pyrolysis is the process of decomposition of a material at high temperatures that takes place in the absence of limited air or air. The purpose of this study is to provide solutions for how to treat plastic waste and to find out the % yield on the fuel oil produced. The research method carried out is plastic waste cleaned, dried in the sun then pyrolyzed, oil yield measured in volume and then calculated % yield using the % yield formula. The results of this study show that the highest % yield at a temperature of 400 oC is 5.0410%, t = 40 minutes, v = 39 ml. Because if the raw material for plastic waste is processed using high temperatures, the carbon chain will be easier to break or break the bond. Where the yield produced is increasing along with the increase in reaction temperature.